Efforts to Improve Student Learning Outcomes Sprint Running Through Traditional Games (Gobak Sodor) - Putri, Aprillia Maharani; Apriani, Leni (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to determine the increase in student learning outcomes Sprint Running through traditional games (Gobak Sodor). This research was carried out in the 2022/2023 school year. The form of this research was classroom action research. The research subjects were 37 students in class VIII F of MTs Al-Muttaqin Pekanbaru. This research technique is total sampling. The data analysis technique uses a performance test, namely doing Sprint Running practice, then the test results are assessed. From the implementation of the first cycle, the results were 26 students who achieved the KKM score (70%) and 11 students who had not reached the KKM score (30%), followed by the implementation of the second cycle, the results increased with a total of 37 students achieving the KKM score (100%). Thus it can be concluded that there is an increase in student learning outcomes in sprinting through traditional games (gobak sodor) at Mts Al-Muttaqin Pekanbaru with an increase of (100%).